On Irregular Colorings of Unicyclic Graph Family - Arika Indah Kristiana; Dafik Dafik; Qurrotul A’yun; Robiatul Adawiyah; Ridho Alfarisi (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Irregular coloring is a proper coloring and each vertex on a graph must have a different code. The color code of a vertex v is where and is the number of vertices that are adjacent to v and colored i. The minimum k-color used in irregular coloring is called the irregular chromatic number and denoted by . In this paper, we discuss the irregular chromatic number for the bull graph, pan graph, sun graph, peach graph, and caveman graph.